2020
DOI: 10.1007/s11252-020-00942-2
|View full text |Cite
|
Sign up to set email alerts
|

Winter habitat selection of Corvids in an urban ecosystem

Abstract: Urban areas attract birds during the winter when cities provide a predictable source of food and relatively stable weather conditions. However, many other factors determine the occurrence of birds in cities. This study analysed the relationship between corvids wintering in the city of Poznań, in western Poland and habitat features. Each of 32 research site was investigated three times. The most abundant species was the rook (mean = 17.4 individuals/site); the most frequent was the Eurasian magpie (88% of all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 62 publications
1
17
0
Order By: Relevance
“…Our study confirms a pattern previously reported in other European cities that the Eurasian magpie successfully exploits the urban environment, especially green urban habitats, including gardens, orchards or avenues of mature trees that represent crucial nesting habitats in an urban environment (Jokimäki et al 2017, Szala et al 2020). An important adaptation of Eurasian magpies to living in an urban environment may be one of adjusted nesting behaviour (Wang et al 2008), as magpies select higher trees to nest on within urban habitats than in rural habitats.…”
Section: Resultssupporting
confidence: 90%
“…Our study confirms a pattern previously reported in other European cities that the Eurasian magpie successfully exploits the urban environment, especially green urban habitats, including gardens, orchards or avenues of mature trees that represent crucial nesting habitats in an urban environment (Jokimäki et al 2017, Szala et al 2020). An important adaptation of Eurasian magpies to living in an urban environment may be one of adjusted nesting behaviour (Wang et al 2008), as magpies select higher trees to nest on within urban habitats than in rural habitats.…”
Section: Resultssupporting
confidence: 90%
“…We observed that some magpies maintained their territories during the entire year, switching the territorial behaviour from caching seeds to nesting. Magpies usually remain in their nesting territory throughout the year but sometimes they move to other locations and return in spring (Birkhead, 1991; Szala et al., 2020). We showed that nest distribution varied between years, but the dispersal patterns matched the VPs derived from the nest distribution that appeared in the spring after the acorn dispersal season.…”
Section: Discussionmentioning
confidence: 99%
“…To address this goal, we used the interaction among Eurasian magpie ( Pica pica L.) and holm oak ( Quercus ilex L.) as our study system. Magpies are massive acorn scatter‐hoarders, that is, disperse large number of acorns (Martínez‐Baroja et al., 2019) and territorial breeders (Baeyens, 1981; Birkhead, 1991; Szala et al., 2020) that inhabit open landscapes. The holm oak is the most important tree in agroforestry systems in the western Mediterranean Basin (Pulido & Díaz, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that fewer corvid species are urbanized in Finland than in southern and central Europe. For example, we detected the Rook only once even though the species is very abundant in more southern urban areas (e.g., [ 48 , 49 , 79 ]). The Rook became a member of the Finnish avifauna no earlier than the late 1800s, and it is still breeding in only a few sites in Finland [ 80 ].…”
Section: Discussionmentioning
confidence: 99%